Hispanic Health Paradox at the Border: Substance, Alcohol, and Tobacco Use among Latinx Immigrants Seeking Free or Reduced-Cost Care in Southernmost Texas. Issue 4 (April 2020) - Tabler, Jennifer; Mykyta, Laryssa; Chernenko, Alla; Flores, Paloma; Marquez, Alvaro; Saenz, Nancy; Stocker, Rebecca
Abstract : Objective: Although substantial research has explored the Hispanic health paradox (HHP) and suggests that Latinx immigrants experience positive health outcomes relative to those born in the United States, less research has assessed the role of immigration status. Our aim was to examine this role in Latinx health. Methods: Using survey data collected at two free/reduced-cost clinics in southernmost Texas, we examined differences in the mental and self-rated health, substance, alcohol, and tobacco use of low-income patients by undocumented/documented immigrant and US-born/naturalized citizen status (N = 588). Results: Based on ordinary least squares regression results, undocumented Latinx immigrants report lower negative self-rated health (coefficient −0.27, 95% confidence interval −0.50 to −0.01) and lower depressive symptoms (coefficient −0.34, 95% confidence interval −0.67 to −0.02]) compared with their US citizen peers ( P < 0.05). Logistic regression results suggest that undocumented and documented Latinx immigrants do not differ in alcohol, tobacco, or substance use relative to their citizen peers. Conclusions: Despite facing potentially adverse social environments, undocumented Latinx immigrants experience positive health outcomes relative to US-born/naturalized citizen peers. Abstract : This study examines differences in the mental and self-rated health, substance, alcohol, and tobacco use of low-income Latinx patients living in the Lower Rio Grande Valley of southernmost Texas, particularly whether health and substance use behaviors vary based on immigration status.